(untitled) - Ehrman, Douglas S. (Hoboken, N.J., 2006)
Learn both the theory and practice of pairs trading, why it is consistently profitable, and how you can apply the strategies in your own trading with this valuable guide. Author Douglas Ehrman covers pairs trading involving stocks, options on stocks, and futures contracts, and explains how this type of trading allows you to profit from the changing price relationship of securities. In addition to a comprehensive discussion of the theories involved, he also includes practical examples that will to help you put what you've learned into practice.
Keywords: Pairs trading,Stocks